Batch extraction method to estimate total dissolved solids (TDS) release from coal refuse and overburden. (April 2020) - Castillo-Meza, L.E.; Cravotta, C.A.; Tasker, T.L.; Warner, N.R.; Daniels, W.L.; Orndorff, Z.W.; Bergstresser, T.; Douglass, A.; Kimble, G.; Streczywilk, J.; Barton, C.; Fulton, S.; et al.
Abstract: A rapid batch extraction method was evaluated to estimate potential for total dissolved solids (TDS) release by 65 samples of rock from coal and gas-bearing strata of the Appalachian Basin in eastern USA. Three different extractant solutions were considered: deionized water (DI), DI equilibrated with 10% CO2 atmosphere (DI + CO2 ), or 30% H2 O2 under 10% CO2 (H2 O2 +CO2 ). In all extractions, 10 g of pulverized rock (<0.5-mm) were mixed with 20 mL of extractant solution and shaken for 4 h at 50 rpm and 20–22 °C. The 65 rock samples were classified as coal (n=3), overburden (n = 17), coal refuse that had weathered in the field (n = 14), unleached coal refuse that had oxidized during indoor storage (n = 20), gas-bearing shale (n = 10), and pyrite (n = 1). Extracts were analyzed for specific conductance (SC), TDS, pH, and major and trace elements, and subsequently speciated to determine ionic contributions to SC. The pH of extractant blanks decreased in the order DI (6.0), DI + CO2 (5.1), and H2 O2 +CO2 (2.6). The DI extractant was effective for mobilizing soluble SO4 and Cl salts. The DI + CO2 extractant increased weathering of carbonates and resulted in equivalent or greater TDS than the DI leach of the same material. The H2 O2 +CO2 extractant increased weathering of sulfides (and carbonates) and resulted in the greatest TDS production and lowest pH values. Of the 65 samples, 19 had leachate chemistry data from previous column experiments and 35 were paired to 10 field sites with leachate chemistry data. When accounting for the water-to-rock ratio, TDS from DI and DI + CO2 extractions were correlated to TDS from column experiments while TDS from H2 O2 +CO2 extractions was not. In contrast to column experiments, field SC was better correlated to SC measured from H2 O2 +CO2 extractions than DI extractions. The field SC and SC from H2 O2 +CO2 extractions were statistically indistinguishable for 7 of 9 paired data sets while SC from DI extractions underestimated field SC in 5 of 9 cases. Upscaling comparisons suggest that (1) weathering reactions in the field are more aggressive than DI water or synthetic rainwater extractants used in batch or column tests, and (2) a batch extraction method utilizing 30% H2 O2 (which is mildly acidic without CO2 enrichment) could be effective for identifying rocks that will release high amounts of TDS. Graphical abstract: Image 1 Highlights: 65 samples of rock from coal and gas-bearing strata of the Appalachian Basin tested. Deionized water or 30% H2 O2 under 10% CO2 used to extract TDS from rock samples. Batch extractions compared to column experiments and field leachate chemistry. Batch extraction using 30% H2 O2 correlates to specific conductivity in field. Batch extraction using 30% H2 O2 can identify rocks that produce high levels of TDS.